2004
DOI: 10.1128/jcm.42.2.693-699.2003
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Diversity among Stenotrophomonas maltophilia Strains Despite Their Originating at a Single Hospital

Abstract: The levels of genetic relatedness of 139 Stenotrophomonas maltophilia strains recovered from 105 hospitalized non-cystic fibrosis patients (51% from medical wards, 35% from intensive care units, and 14% from surgical wards) and 7 environmental sources in the same hospital setting during a 4-year period were typed by the pulsed-field gel electrophoresis (PFGE) technique. A total of 99 well-defined distinct XbaI PFGE patterns were identified (Simpson's discrimination index, 0.996). The dendrogram showed a Dice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
58
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 33 publications
11
58
0
3
Order By: Relevance
“…140,320 In general, genotyping analyses have not shown that isolates obtained from the hospital environmental are the same as those recovered from patients, 141,320 and the majority of non-CF patients infected with S. maltophilia had genetically distinct strains. 321 None of 24 S. maltophilia isolates recovered from water, taps, and sinks in patient rooms matched the strains recovered from individuals with CF.…”
Section: Iiid2 Healthcare Sources: Water Surfaces Equipment Airmentioning
confidence: 99%
“…140,320 In general, genotyping analyses have not shown that isolates obtained from the hospital environmental are the same as those recovered from patients, 141,320 and the majority of non-CF patients infected with S. maltophilia had genetically distinct strains. 321 None of 24 S. maltophilia isolates recovered from water, taps, and sinks in patient rooms matched the strains recovered from individuals with CF.…”
Section: Iiid2 Healthcare Sources: Water Surfaces Equipment Airmentioning
confidence: 99%
“…Many typing approaches have revealed that this species is of high genodiversity. Genotyping of isolates from hospitalized CF and non-CF patients by PFGE or randomly amplified polymorphic DNA PCR revealed a high degree of diversity with changes in the strains consecutively isolated from CF patients (18,38,70,71). A multilocus enzyme electrophoresis scheme has been proposed for investigations of hospital epidemiology (60).…”
Section: Vol 191 2009 Mlst For S Maltophilia Population Structure mentioning
confidence: 99%
“…Although rarely associated with septic shock, S. maltophilia commonly causes persistent bacteremia and is frequently associated with respiratory tract and catheter-related infections. An analysis of 139 isolates from 105 non-CF patients established that S. maltophilia was a cause of infection in the central nervous system, bone, bloodstream, and urinary tract, as well as the respiratory tract (37). Many case reports have demonstrated the potential of S. maltophilia to cause invasive infection as an opportunistic pathogen in immunocompromised patients (24) or when it is inadvertently introduced into a normally sterile site (20).…”
mentioning
confidence: 99%